Website-Based Book Sales Information System at Maktabah Bin Taajir Bookstore - Muhammad Rifqi Nugraha; Deddy Kurniawan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Maktabah Bin Taajir Bookstore is a bookstore that offers a variety of books, including fiqh, translated Islamic books, and others. Currently, the system used is still conventional, with data stored in paper format, causing issues in data management and report generation. To address these problems, the author has developed a book sales information system using the Waterfall Method. The Waterfall Method is a sequential software development approach, starting from requirement analysis, design, implementation, testing, and maintenance. This method was chosen because it helps developers in developing a structured system, following a step-by-step process from planning to implementation. The result of this research is a web-based book sales information system that is expected to facilitate and assist the Admin in managing book data, publisher data, and sales reports, while improving efficiency and effectiveness in the management process